2022
DOI: 10.1039/d2ra04433a
|View full text |Cite
|
Sign up to set email alerts
|

Pickering emulsion technology based on the concept of “the combination of medicine and adjuvant” to enhance the oxidation stability of volatile oils in solid preparations—taking Lingzhu Pulvis as an example

Abstract: The antioxidant properties of the volatile oil of Acorus calamus in Lingzhu Pulvis may be enhanced by the introduction of Pickering emulsion technology based on the concept of “the combination of medicine and adjuvant”.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Near-Infrared Spectrum. The ANTIRIS II Fourier Transform Near Infrared Spectrometer (Thermo Fisher Scientific (USA)) was employed to measure the near-infrared spectrum (NIRS) of AT-EO, modified amber suspension (7.5 μg/mL), and Pickering emulsion samples, according to the method conducted by Peng et al 22 The samples were adjusted to the accompanying quartz sample cup and ensured that the cup bottom was fully submerged. The NIRS spectrum was acquired at room temperature with 32 scan repetitions, a resolution of 8 cm −1 , a gain of 4×, and a spectral range of 4000−10,000 cm −1 .…”
Section: Characterization Of Pickering Emulsion 2331 Emulsion Typementioning
confidence: 99%
See 1 more Smart Citation
“…Near-Infrared Spectrum. The ANTIRIS II Fourier Transform Near Infrared Spectrometer (Thermo Fisher Scientific (USA)) was employed to measure the near-infrared spectrum (NIRS) of AT-EO, modified amber suspension (7.5 μg/mL), and Pickering emulsion samples, according to the method conducted by Peng et al 22 The samples were adjusted to the accompanying quartz sample cup and ensured that the cup bottom was fully submerged. The NIRS spectrum was acquired at room temperature with 32 scan repetitions, a resolution of 8 cm −1 , a gain of 4×, and a spectral range of 4000−10,000 cm −1 .…”
Section: Characterization Of Pickering Emulsion 2331 Emulsion Typementioning
confidence: 99%
“…In a previous study, we investigated the emulsification effect of medicinal powders in Lingzhu Pulvis and found that pearl powder was a suitable O/W-type stabilizer. Subsequent studies have indicated that the Pickering emulsion stabilized by pearl powder could improve volatilization and oxidation of AT-EO. Contrastingly, amber, owing to its poor water solubility was proved to be a unsuitable O/W-type stabilizer…”
Section: Introductionmentioning
confidence: 99%